FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS HIDUP LANSIA DI PANTI WERDHA WILAYAH TANGERANG SELATAN - Dewi Angraini; Ella Nurlaela Hadi (Jurnal Kesehatan STIKes IMC Bintaro, 2017)
Quality of life is the functional condition of the elderly which includes physical health, psychological health, elderly social relationships, as well as sexual activity, and environmental conditions. Population growth rate in South Tangerang is the fastest (3.36%) compared to other regencies / cities in Banten province. Life expectancy in 2015 is the highest compared to other regions in Banten which reached 72.2 years. Approximately 5% of the population in South Tangerang is over 60 years old (BPS, 2016) and 0.8% of the total elderly people in Tangerang Selatan prefer to stay in the orphanage because they feel have many friends for activities, worshiping and eliminate loneliness. This study aims to determine the quality of life of the elderly and the factors related to the quality of life of elderly living in the werdha orphanage of Tangerang Selatan region. Cross-sectional study design was used in 144 selected randomly elderly from 4 orphanages in South Tangerang. Data collected using interview method using questionnaires that have been tested for validity and reliability, and analyzed using multiple logistic regression test. The results showed that 74.3% of elderly people living in the orphanage of Tangerang Selatan have quality of life, elderly education is a factor related to the quality of life of the elderly (p = 0,003; OR 3,22; 95% CI 1,49-6, 97). Elderly with a high education has a 3,2 times more quality of life than the poorly educated elderly.